The Role of The BI Rate in Maintaining The Stability of The Sharia Financial System - Ade Aisah Putri Insani Chaniago; Sugiyat, Sugiyat (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This article aims to analyze the role of the BI Rate on Islamic banking stability indicators, namely Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR), as well as to examine its contribution in strengthening the resilience of the Islamic financial system during periods of global crisis. This research employs a descriptive qualitative method with a document study approach, using secondary data obtained from annual reports of Bank Indonesia, the Financial Services Authority (OJK), and related scholarly publications. The research sample covers the BI Rate trend and Islamic banking indicators during the 2019–2023 period. The findings reveal that BI Rate fluctuations affect the performance of Islamic banks, particularly in reducing NPF levels and sustaining capital adequacy (CAR), although its relationship with FDR remains volatile. These results highlight that the BI Rate remains relevant as a stabilization instrument despite its limitations in the Islamic financial context. This study contributes to strengthening the literature on the interaction between conventional monetary policy and Islamic financial system stability, while also providing insights for regulators in formulating adaptive and sustainable policies. Therefore, the results emphasize the importance of integrating monetary policy in ensuring the continuity and resilience of the Islamic financial system amid global economic dynamics.